2016
DOI: 10.1371/journal.ppat.1005708
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Manipulation of NK Cell Regulatory Activity Increases Susceptibility to Listeria monocytogenes Infection

Abstract: Natural killer (NK) cells produce interferon (IFN)-γ and thus have been suggested to promote type I immunity during bacterial infections. Yet, Listeria monocytogenes (Lm) and some other pathogens encode proteins that cause increased NK cell activation. Here, we show that stimulation of NK cell activation increases susceptibility during Lm infection despite and independent from robust NK cell production of IFNγ. The increased susceptibility correlated with IL-10 production by responding NK cells. NK cells produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 66 publications
(97 reference statements)
12
62
1
Order By: Relevance
“…2 B). This result is consistent with previous demonstrations of the importance of early innate sources of IFN-γ for effective immune responses in systemic L. monocytogenes infection (Dunn andNorth, 1991 Ladel et al, 1996;Thäle and Kiderlen, 2005), although NKs have also been shown to reduce resistance during early phases of Listeria infection after intravenous inoculation of WT mice (Teixeira and Kaufmann, 1994;Viegas et al, 2013;Clark et al, 2016).…”
Section: The Gut Microbiota Provides Nonredundant Protection Against supporting
confidence: 92%
“…2 B). This result is consistent with previous demonstrations of the importance of early innate sources of IFN-γ for effective immune responses in systemic L. monocytogenes infection (Dunn andNorth, 1991 Ladel et al, 1996;Thäle and Kiderlen, 2005), although NKs have also been shown to reduce resistance during early phases of Listeria infection after intravenous inoculation of WT mice (Teixeira and Kaufmann, 1994;Viegas et al, 2013;Clark et al, 2016).…”
Section: The Gut Microbiota Provides Nonredundant Protection Against supporting
confidence: 92%
“…Expression of p60 by Lm was also shown to boost activation and IFNγ secretion by NK cells co-cultured with infected BMDC (21,23). The ability to promote NK cell activation appears to benefit Lm because IFNγ secreting NK cells responding to p60/L1S rapidly switch to secretion of IL-10 (21).…”
Section: Discussionmentioning
confidence: 94%
“…Expression of p60 by Lm was also shown to boost activation and IFNγ secretion by NK cells co-cultured with infected BMDC (21,23). The ability to promote NK cell activation appears to benefit Lm because IFNγ secreting NK cells responding to p60/L1S rapidly switch to secretion of IL-10 (21). IL-10 has been argued both to promote anti-tumor resistance in the B16.F10 model (32), and to promote growth of B16.F10 melanoma cells (34).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations